Gastric lesions associated with the infection of Anisakidae nematodes in a dwarf sperm whale Kogia sima (Owen, 1866) stranded in the north coast of Brazil - Gisele C.C. Seade; David F. Conga; Tiago S. Santos; Marcio O. Moura; Diana M. de Farias; Lana O. Silva; Alexandra F. Costa; Tayanna M. Amaral; Maura M. de Souza; Renata Emin-Lima; Alessandra Scofield; Gabriela Riet-Correa; et al. (International Journal for Parasitology: Parasites and Wildlife)
The present study aimed to describe gastric lesions associated with parasitism by different nematodes of the family Anisakidae in a stranded specimen of dwarf sperm whale (Kogia sima) on the northeast coast of the State of Pará, northern Brazil. Specimens of helminths and samples of stomach tissue were collected from a dwarf sperm whale, stranded on Humaitá beach, State of Pará, Brazil. Stomach showed areas of erosion and ulcers, with the mucosa covered by fibrinonecrotic material containing bacteria and inflammatory infiltrate predominantly comprising polymorphonuclear cells. Granulomas were also found in the submucosa, characterized by central areas of necrosis and hemorrhage, and cross sections of nematodes were observed. Fourth-stage larvae of the genus Pseudoterranova, two morphotypes of fourth-stage larvae of the genus Anisakis and adult specimens of Skrjabinisakis paggiae were morphologically identified. Molecular and phylogenetic analyzes confirmed the identity of the partial sequences of the cox2 mtDNA gene for adult specimens of S. paggiae. This study contributes to our understanding of the distribution of different of anisakids in K. sima and about the gastric lesions associated with these nematodes, in addition to expanding the knowledge about the occurrence of this aquatic mammal recorded for the first time in the northern region of Brazil.